Prince of Persia. - Burt, Andy.
Ubisoft returns with a brand-new game set in the Sands of Time universe to coincide with the upcoming film adaptation starring Jake Gyllenhaal.
Keywords: Ubisoft (Firm); Prince of Persia, the sands of time (Motion picture); Prince of Persia (Game); Video-game movies